2014
DOI: 10.1371/journal.pone.0113836
|View full text |Cite
|
Sign up to set email alerts
|

By-Catch of Grey Seals (Halichoerus grypus) in Baltic Fisheries—A Bayesian Analysis of Interview Survey

Abstract: Baltic seals are recovering after a population decline. The increasing seal stocks cause notable damage to fisheries in the Baltic Sea, with an unknown number of seals drowning in fishing gear every year. Thus, sustainable seal management requires updated knowledge of the by-catch of seals—the number of specimens that die in fishing gear. We analyse the by-catch of grey seals (Halichoerus grypus) in Finland, Sweden, and Estonia in 2012. We collect data with interviews (35 in Finland, 54 in Sweden, and 72 in Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 13 publications
0
17
0
3
Order By: Relevance
“…Researchers took part to the field work (tagging live animals and taking samples from dead ones) during years 2011–2013 and they often had possibility to verify the reliability of the data. Although the fishermen’s motivation to report by-catch has generally been low in Finland [ 18 ], the volume of by-catch reported in this study is high and comparable between the two periods (2008–2010 and 2011–2013). It is therefore likely that the volumes of by-catch detected in our study are not underrated.…”
Section: Methodsmentioning
confidence: 67%
See 2 more Smart Citations
“…Researchers took part to the field work (tagging live animals and taking samples from dead ones) during years 2011–2013 and they often had possibility to verify the reliability of the data. Although the fishermen’s motivation to report by-catch has generally been low in Finland [ 18 ], the volume of by-catch reported in this study is high and comparable between the two periods (2008–2010 and 2011–2013). It is therefore likely that the volumes of by-catch detected in our study are not underrated.…”
Section: Methodsmentioning
confidence: 67%
“…In addition to hunting, by-catch mortality may be another significant component of the anthropogenic mortality of seal populations. Estimated annual by-catch of the Baltic grey seal is in the order of 2000 animals or more [ 18 ] but for ringed seals the magnitude is unknown. An information gap regarding by-catch and its mitigation methods in coastal and small scale fisheries has been recognized globally [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current knowledge on the level of by-catches of Baltic seal species is limited to a few dedicated studies which suggest that this factor can be substantial. An analysis of reported by-caught grey seals showed that approximately 2,000 grey seals are caught annually in the Baltic fisheries (Vanhatalo et al 2014), but numbers of by-caught ringed seals and harbour seals are not known.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Прилов -неумышленный вылов морских млекопитающих или определённых видов рыб [Soykan et al 2008] -получил относительно небольшое внимание со стороны биологов и экологов [Read, Drinke, Northridge 2006;Vanhatalo et al 2014;Johnston et al 2015]. Однако проведённые исследования показывают, что прилов оказывает значительное влияние на локальные морские экосистемы, сокращая популяции высших хищников.…”
Section: Introductionunclassified